Evidence Basis for Regional Anesthesia in Ambulatory Arthroscopic Knee Surgery and Anterior Cruciate Ligament Reconstruction: Part II. (February 2019) - Sehmbi, Herman; Brull, Richard; Shah, Ushma Jitendra; El-Boghdadly, Kariem; Nguyen, David; Joshi, Girish P.; Abdallah, Faraj W.
Abstract : BACKGROUND: Adductor canal block (ACB) has emerged as an effective analgesic regional technique for major knee surgeries in the last decade. Its motor-sparing properties make it particularly attractive for ambulatory knee surgery, but evidence supporting its use in ambulatory arthroscopic knee surgery is conflicting. This systematic review and meta-analysis evaluates the analgesic effects of ACB for ambulatory arthroscopic knee surgeries. METHODS: We conducted a comprehensive search of electronic databases for randomized controlled trials examining the analgesic effects of ACB compared to control or any other analgesic modality. Both minor arthroscopic and anterior cruciate ligament reconstruction (ACLR) surgeries were considered. Rest and dynamic pain scores, opioid consumption, opioid-related adverse effects, time to first analgesic request, patient satisfaction, quadriceps strength, and block-related complications were evaluated. Data were pooled using random-effects modeling. RESULTS: Our search yielded 10 randomized controlled trials comparing ACB with placebo or femoral nerve block (FNB); these were subgrouped according to the type of knee surgery. For minor knee arthroscopic surgery, ACB provided reduced postoperative resting pain scores by a mean difference (95% confidence interval) of −1.46 cm (−2.03 to −0.90) ( P < .00001), −0.51 cm (−0.92 to −0.10) ( P = .02), and −0.48 cm (−0.93 to −0.04) ( P = .03) at 0, 6, and 8 hours, respectively, compared to control. Dynamic pain scores were reduced by a mean difference (95% confidence interval) of −1.50 cm (−2.10 to −0.90) ( P < .00001), −0.50 cm (−0.95 to −0.04) ( P = .03), and −0.59 cm (−1.12 to −0.05) ( P = .03) at 0, 6, and 8 hours, respectively, compared to control. ACB also reduced the cumulative 24-hour oral morphine equivalent consumption by −7.41 mg (−14.75 to −0.08) ( P = .05) compared to control. For ACLR surgery, ACB did not provide any analgesic benefits and did not improve any of the examined outcomes, compared to control. ACB was also not different from FNB for these outcomes. CONCLUSIONS: After minor ambulatory arthroscopic knee surgery, ACB provides modest analgesic benefits, including improved relief for rest pain, and reduced opioid consumption for up to 8 and 24 hours, respectively. The analgesic benefits of ACB are not different from placebo or FNB after ambulatory ACLR, suggesting a limited role of both blocks in this procedure. Paucity of trials dictates cautious interpretation of these findings. Future studies are needed to determine the role of ACB in the setting of local anesthetic instillation and/or graft donor-site analgesia.